1992
DOI: 10.1136/oem.49.10.736
|View full text |Cite
|
Sign up to set email alerts
|

Follow up study of renal tubular dysfunction and mortality in residents of an area polluted with cadmium.

Abstract: Urinary #,-microglobulin (/,-m) concentration was determined by radioimmunoassay with Phadebas /2-microtests (Pharmacia/Shionogi, Osaka), and urinary total amino nitrogen concentration by the trinitrobenzene sulphonic acid method.In August 1990, we checked vital status of the 230 participants in the health surveys. The observation period was from the date of the initial examination to the date of death or transfer or 1 August 1990. Of 230 subjects in the cohort, 88 had died and three had moved out of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
2
20
1
Order By: Relevance
“…Mortality risk was increased by 40-80 % in people with signs of Cd-linked tubular injury (Iwata et al 1992;Nakagawa et al 1993Nakagawa et al , 1999Nakagawa and Nishijo 1996). Urinary excretion levels of Cd and β 2-microglobulin were associated with mortality risk in a dose-dependent manner .…”
Section: Renal CD Toxicities and Adverse Health Outcomesmentioning
confidence: 86%
“…Mortality risk was increased by 40-80 % in people with signs of Cd-linked tubular injury (Iwata et al 1992;Nakagawa et al 1993Nakagawa et al , 1999Nakagawa and Nishijo 1996). Urinary excretion levels of Cd and β 2-microglobulin were associated with mortality risk in a dose-dependent manner .…”
Section: Renal CD Toxicities and Adverse Health Outcomesmentioning
confidence: 86%
“…In contrast, it was reported that the mortality among male subjects with urinary RBP concentrations ³4 mg/l (measured by the single radial immunodiusion method) was signi®cantly higher than that among those with urinary RBP concentrations <4 mg/l in a Cd-polluted area in Ishikawa Prefecture (Nakagawa et al 1987). These contradictory ®ndings prompted us to perform historical cohort studies in Cd-polluted areas in Nagasaki and Akita Prefectures (Iwata et al 1991(Iwata et al , 1992. The result was that in both male and female subjects, urinary b 2 M (U-b 2 M) concentration was a signi®cant predictor of mortality independent of age (Iwata et al 1991).…”
Section: Introductionmentioning
confidence: 96%
“…Cd emissions into the environment are normally continuous between the three main environmental compartments, air, water and soil. The majority of Cd exposure arises from ingestion of food substances due to uptake of Cd by plants from fertilizers, sewage, sludge, manure and atmospheric deposition (Anderson et al, 1988;Hotz et al, 1989;Lauwerys et al, 1991;Iwata et al, 1992;Bernard et al, 1992;Ikeda et al, 2000). Human uptake of Cd is mainly through cigarette smoking, food and water intake.…”
Section: Introductionmentioning
confidence: 99%